They're always there for me! Friendship and meaning in young people's lives? - O'Rourke, John (Scand J Psychol, 2019)
What gives individuals’ lives meaning is one of the bigger questions confronted by community members? Making sense of our lives and determining what it is that provides us with direction, strength, or commitment is no simple task and even more so in western consumerist societies where so many experiences appear accessible. Finding ways to elicit thoughtful responses from research participants, has led to varied approaches to this increasingly rich research area. An encouraging method is to use digital photography to extract information on what it is that captures participants’ ‘mind's eye’ when reflecting on meaning in their lives. In this article, a pilot study using a combination of digital photography and descriptive narratives was established to explore the thoughts of 174 year seven students in a private West Australian school on what provided their lives with meaning both in school and outside of school. The photos and narratives were explored for themes and while many categories were identified, it was apparent that relationships were the strongest source of meaning in their lives.